Hierarchical TiO2 nanofibres as photocatalyst for CO2 reduction: Influence of morphology and phase composition on catalytic activity. (September 2016) - Reñones, Patricia; Moya, Alicia; Fresno, Fernando; Collado, Laura; Vilatela, Juan J.; de la Peña O'Shea, Víctor A.
Graphical abstract: Highlights: TiO2 nanofibres have been successfully prepared combining electrospinning and sol–gel methods. Fibres are composed of hierarchically interconnected TiO2 nanoparticles with large interfaces. Fast charge transport and transfer are observed from EIS measurements in fibre catalysts. Decreased e − -h + recombination combined with electrochemical properties lead to high CO2 photocatalytic reduction activities. Abstract: In this research work, the gas phase CO2 photocatalytic reduction using water as electron donor has been performed using hierarchical assemblies of mesoporous TiO2 1-D nanofibres synthesised by a combination of electrospinning and sol–gel methods. In order to compare the effect of the crystallisation step on oxygen vacancies and conductivity, two different annealing conditions have been undertaken: under a high Ar flow ("TiO2 Fibres-A" sample) and under static Ar ("TiO2 Fibres B" sample). Moreover, these materials have been compared with individualised TiO2 nanoparticles prepared by a sol-gel procedure. CO and H2 are detected as major products with all photocatalysts, with lower amounts of CH4 and CH3 OH. The TiO2 nanofibres exhibit better results than the sol-gel photocatalyst, behaviour that may be ascribed to an improved nanocrystals connection, which favours a fast charge transport along the grain boundaries, as measured by electrochemical impedance spectroscopy (EIS). The highest CO2 reduction activity is achieved with the TiO2 Fibres B catalyst, which gives rise to ca. 4 and 2.5 times higher H2 and CO production, respectively, than the TiO2 Fibres-A one. This sample is composed of a mixture of anatase and rutile crystalline phases (80:20), leading to a decrease in the electron-hole recombination rate observed by photoluminescence (PL) measurements.